GE_GERICHTE P/19972/2010 vom 4. April 2013 - GE Cour de justice (2013)
INFRACTIONS CONTRE L'HONNEUR; DIFFAMATION; CALOMNIE; RESPONSABILITÉ RESTREINTE(DROIT PÉNAL); DOMMAGE; TORT MORAL; AVOCAT; HONORAIRES | CP.173.1; CP.174.1; CP.19; CO.49; CPP.433.1